Filantropi Berbasis Pendidikan Kewarganegaraan: Pembelajaran Untuk Memperkuat Karakter Kepedulian Sosial Warga Negara - Kusnadi, Kusnadi (University of Muhammadiyah Malang, 2024)
This research explores the role of civic education-based philanthropy in strengthening the social care character of citizens. Using literature study methods, this research examines various theories, concepts, and practices of philanthropy in the context of citizenship education. The main focus of the research is on how citizenship learning can shape characters who care about social welfare through philanthropic action. Literature analysis shows that the integration of philanthropy in citizenship learning can increase social awareness and civic responsibility while strengthening the values of solidarity, empathy, and social participation. It is hoped that the results of this research can contribute to the development of educational strategies that focus on building social caring character through a philanthropic approach.